Military medical ethics for the 21st century - Gross, Michael L.; Carrick, Don (Military and defence ethics, 2013)
In this book the authors explore the practice of battlefield bioethics, medical neutrality and treatment of the wounded, enhancement technologies for war fighters, the potential risks of dual-use biotechnologies, patient rights for active duty personnel, military medical research and military medical ethics education in the 21st Century.